2020
DOI: 10.7150/thno.46428
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics Analysis of Computed Tomography helps predict poor prognostic outcome in COVID-19

Abstract: Rationale: Given the rapid spread of COVID-19, an updated risk-stratify prognostic tool could help clinicians identify the high-risk patients with worse prognoses. We aimed to develop a non-invasive and easy-to-use prognostic signature by chest CT to individually predict poor outcome (death, need for mechanical ventilation, or intensive care unit admission) in patients with COVID-19. Methods: From November 29, 2019 to February 19, 2020, a total of 492 patients with COVID-19 from four centers were retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
98
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(105 citation statements)
references
References 47 publications
2
98
0
2
Order By: Relevance
“…Recently, some radiomics-based AI models have been developed for aided diagnosis, efficacy evaluation, or prognosis analysis of COVID-19. Wu et al [ 30 ] developed a CT-based signature to perform prognostic analysis in patients with COVID-19. Fang et al [ 31 ] developed a radiomics model to predict COVID-19 pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some radiomics-based AI models have been developed for aided diagnosis, efficacy evaluation, or prognosis analysis of COVID-19. Wu et al [ 30 ] developed a CT-based signature to perform prognostic analysis in patients with COVID-19. Fang et al [ 31 ] developed a radiomics model to predict COVID-19 pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Our results support the application of radiomics to assist with diagnosis of COVID-19 pneumonia. The recent development of radiomics has provided a new research paradigm in clinical studies [ 35 , 36 ], and there have already been radiomics studies published for COVID-19 survival prognosis and illness severity identification [ [12] , [13] , [14] , [15] ]. However, current radiomics studies on the differentiation of COVID-19 from other types of viral pneumonia with clinical symptoms and CT signs similar to those of COVID-19, and the evaluation of radiomic feature among different classifiers on COVID-19, are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the region of interest (ROI) for pneumonia lesions delineated by radiologists, radiomics may provide additional knowledge for survival prognosis and classification of illness severity for COVID-19 pneumonia [ [12] , [13] , [14] , [15] ]. The latest analytical tool of radiomics, Pyradiomics, has paved the way for standardised radiomics analysis [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…And Chen et al found that radiomics model based on CT images is a feasible and promising method for monitoring poor prognostic outcome in patients with COVID-19 [17][18] . Besides, radiomics has been also used to identify focal organizing pneumonia and peripheral lung adenocarcinoma [19] .…”
Section: Introductionmentioning
confidence: 99%